2007
DOI: 10.1289/ehp.9860
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Exposure to Brominated Flame Retardant BDE-47 Reduces Long-Term Potentiation and Postsynaptic Protein Levels in Mouse Hippocampus

Abstract: BackgroundIncreasing environmental levels of brominated flame retardants raise concern about possible adverse effects, particularly through early developmental exposure.ObjectiveThe objective of this research was to investigate neurodevelopmental mechanisms underlying previously observed behavioral impairments observed after neonatal exposure to polybrominated diphenyl ethers (PBDEs).MethodsC57Bl/6 mice received a single oral dose of 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47) on postnatal day (PND) 10 (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
102
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 43 publications
(57 reference statements)
3
102
1
Order By: Relevance
“…Somewhat in contrast with these findings, Dingemans et al (2007) reported that increased vesicular catecholamine release in PC-12 cells. The release of the neuropeptide vasopressin from hypothalamic preparations (tissue punches from the supraoptic and paraventricular nuclei) was shown to be inhibited by DE-71, BDE-47 and BDE-77 at micromolar concentrations (Coburn et al 2007).…”
Section: Biochemical Studies In Vitromentioning
confidence: 60%
See 2 more Smart Citations
“…Somewhat in contrast with these findings, Dingemans et al (2007) reported that increased vesicular catecholamine release in PC-12 cells. The release of the neuropeptide vasopressin from hypothalamic preparations (tissue punches from the supraoptic and paraventricular nuclei) was shown to be inhibited by DE-71, BDE-47 and BDE-77 at micromolar concentrations (Coburn et al 2007).…”
Section: Biochemical Studies In Vitromentioning
confidence: 60%
“…Micromolar concentrations of BDE-99 were reported to increase Ca ++ concentrations in rat astrocytes, PC-12 cells and human macrophages Smolnikar et al 2001 (abstract)]. Similarly, BDE-47 (20 uM) was reported to increase [Ca ++ ] in PC-12 cells (Dingemans et al 2007). In contrast, DE-71 (30 uM) did not cause any Ca ++ elevation in cerebellar granule cells (Reistad et al 2006), and octaBDE (10-40 uM) did not alter Ca ++ levels in mouse thymocytes (Sandal et al 2004).…”
Section: Biochemical Studies In Vitromentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies have shown structural and functional alterations in the brains of PBDE-exposed animals. Brain changes have also been observed in the expression of genes and proteins involved in synapse and axon formation, neuronal morphology, cell migration, and synaptic plasticity [7,11,12]. Cellular and molecular mechanisms affected include neuronal viability (via apoptosis and oxidative stress), neurotransmitter release/uptake, neurotransmitter receptors and ion channels, calcium homeostasis, and intracellular signaling pathways [9].…”
Section: Introductionmentioning
confidence: 99%
“…In general, previous studies of PBDEs in vitro have incorporated micromolar (lM) levels in the culture media, although several reports have used nanomolar (nM) levels (Barber et al, 2006;Cantón et al, 2006;Dingemans et al, 2007Dingemans et al, , 2008Fery et al, 2009;Giordano et al, 2008Giordano et al, , 2009He et al, 2008aHe et al, ,b, 2009Hu et al, 2007;Madia et al, 2004;Mercado-Feliciano and Bigsby, 2008;Peters et al, 2004Peters et al, , 2006Stavenes Andersen et al, 2009;Song et al, 2009;Stapleton et al, 2009;Tagliaferri et al, 2010;Zhang et al, 2007). None of these studies measured the cellular PBDE concentrations but it is assumed that the concentrations used may not be environmentally relevant because they are much higher than the picomolar (pM) or lower levels typically found in environmental water or body fluids (Frederiksen et al, 2009;Gill et al, 2004;Streets et al, 2006;Wu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%